Iron deficiency in pulmonary arterial hypertension: perspectives - Marceau Quatredeniers; David Montani; Alain Cohen‐Solal; Frédéric Perros (Pulmonary Circulation)
In left heart failure, iron supplementation (IS) is a first‐line treatment option, regardless of anemia. Pulmonary arterial hypertension (PAH), a rare disease leading to right heart failure, is also associated with iron deficiency. While it is a much debated topic, recent evidence demonstrate that restoration of iron stores results in improved right ventricular function and exercise tolerance. Hence, IS may also be considered as an option in the treatment of PAH.